Multikulturalisme di SMA Muhammadiyah Studi Kasus: Pelayanan Terhadap Siswa Non Muslim di SMA Muhammadiyah Kota Jayapura - Khoirunnisa, Ulfa; Sileuw, Marwan; Rofiki, A.Arif; Umkabu, Talabuddin; Muhyidin, Syaiful (Equilibrium: Jurnal Pendidikan, 2025)
Multicultural education is an education that seriously considers the background of students from various aspects such as ethnicity, race, religion, and culture. SMA Muhammadiyah Jayapura City is a school established by the Muhammadiyah organization based on Islamic ideology, but the school is still open to anyone who wants to study at the school, including non-Muslim students. This can create its own challenges in providing fair and inclusive services for non-Muslim students. This study aims to (1) describe the variety of multiculturalism in SMA Muhammadiyah Jayapura City (2) describe the services to non-Muslim students at SMA Muhammadiyah Jayapura City (3) describe the behavior shown by non-Muslim students at SMA Muhammadiyah Jayapura City. Through a qualitative approach and data collection through in-depth interviews and observations, this study gained an in-depth understanding of the variety of multiculturalism, services, and behaviors of non-Muslim students. Data analysis techniques included data reduction, data presentation, and conclusion. The validity of the data was carried out by triangulating sources and techniques. The results of the study show that SMA Muhammadiyah Jayapura shows multicultural diversity in religious (Islamic-Christian), ethnic (Javanese, Papuan, etc.), and economic aspects (ability-based tuition policy). However, services for non-Muslim students still have structural gaps: (1) The unavailability of special worship spaces and non-Muslim religious teachers, contrary to Law No. 20 of 2003; (2) Although consistent in academic equality (reliability), non-Muslim students are only required to attend PAI lessons without a substantial understanding. On the other hand, schools provide responsive services (minority religious holidays, schedule adjustments), justice guarantees (freedom not to wear the hijab), and empathy (tuition discounts/meal vouchers). The response of non-Muslim students was characterized by harmonious interaction, compliance with the rules (despite being constrained by attendance due to distance), and active tolerance by respecting Muslim worship and participating in Islamic celebrations.